Antecedents of B2C Channel Satisfaction and Preference: Validating e-Commerce Metrics - Devaraj, Sarv; Fan, Ming; Kohli, Rajiv (Information systems research, 2002)
Although electronic commerce (EC) has created new opportunities for businesses as well as consumers, questions about consumer attitudes toward Business-to-Consumer (B2C) e-commerce vis-à-vis the conventional shopping channels continue to persist. This paper reports results of a study that measured consumer satisfaction with the EC channel through constructs prescribed by three established frameworks, namely the Technology Acceptance Model (TAM), Transaction Cost Analysis (TCA), and Service Quality (SERVQUAL). Subjects purchased similar products through conventional as well as EC channels and reported their experiences in a survey after each transaction. Using constructs from the three frameworks, a model was constructed and tested to examine the determinants of the EC channel satisfaction and preference using the survey data. Structural equation model analyses indicate that metrics tested through each model provide a statistically significant explanation of the variation in the EC consumers' satisfaction and channel preference. The study found that TAM componentsperceived ease of use and usefulnessare important in forming consumer attitudes and satisfaction with the EC channel. Ease of use also was found to be a signi.cant determinant of satisfaction in TCA. The study found empirical support for the assurance dimension of SERVQUAL as determinant in EC channel satisfaction. Further, the study also found general support for consumer satisfaction as a determinant of channel preference.